2018
DOI: 10.1101/468223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Composition of the Survival Motor Neuron (SMN) complex in Drosophila melanogaster

Abstract: Spinal Muscular Atrophy (SMA) is caused by homozygous mutations in the human survival motor neuron 1 (SMN1) gene. SMN protein has a well-characterized role in the biogenesis of small nuclear ribonucleoproteins (snRNPs), core components of the spliceosome. SMN is part of an oligomeric complex with core binding partners, collectively called Gemins. Biochemical and cell biological studies demonstrate that certain Gemins are required for proper snRNP assembly and transport. However, the precise functions of most G… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 97 publications
2
6
0
Order By: Relevance
“…Gem5 and Lsm10 were also present in precipitates but fell just outside of our stringent cut-off criteria ( Figure 2C). These findings are in good agreement with recent AP-MS results obtained from Drosophila embryos expressing Smn-FLAG [49]. Collectively, our results provide strong evidence that dTgs1 physically associates with the Drosophila Smn complex in vivo, suggesting a parallel functional interaction.…”
Section: Dtgs1 Physically Interacts With the Smn Complexsupporting
confidence: 92%
See 3 more Smart Citations
“…Gem5 and Lsm10 were also present in precipitates but fell just outside of our stringent cut-off criteria ( Figure 2C). These findings are in good agreement with recent AP-MS results obtained from Drosophila embryos expressing Smn-FLAG [49]. Collectively, our results provide strong evidence that dTgs1 physically associates with the Drosophila Smn complex in vivo, suggesting a parallel functional interaction.…”
Section: Dtgs1 Physically Interacts With the Smn Complexsupporting
confidence: 92%
“…Interestingly, the fly SMN complex contains only four bona fide Gemin proteins (Gem2, Gem3, Gem4/Glos and Gem5/Rig) [49,50,74]. The existence of potential homologs of Gem6, 7 and 8 was postulated by [50] but was not confirmed in a subsequent study [49]. Our AP/MS analyses of embryo extracts showed that Smn strongly co-precipitates with GFP-dTgs1.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Generally, RBPs comprise RNA-binding domains (RBD) and protein-protein interaction modules (Ellisdon et al, 2012;Katibah et al, 2013;Lunde et al, 2007;Yang et al, 2012), such that the combination of distinct domains provides multiple features to these factors. Gemin5 is a predominantly cytoplasmic RBP that forms part of the survival of motor neuron (SMN) complex in metazoan organisms (Battle et al, 2006;Matera et al, 2019). This multi-protein complex plays a critical role in the biogenesis of small nuclear ribonucleoproteins (snRNPs) (Lau et al, 2009), the components of the splicing machinery.…”
Section: Highlightsmentioning
confidence: 99%